Physicochemical Changes In The Fermentation And Drying of Cocoa Materials In Colombia (2022)
Post-harvest processes in cocoa beans are decisive for the development of specific flavors. However, these reactions are subject to the initial characteristics, making it important to know the different conditions that occur in each material, and thus ensure that the possible mixtures during fermentation are the most appropriate. In accordance with the above, the need arises to carry out this study, which aims to characterize the physicochemical variables during the fermentation and drying of cocoa materials. Ten materials were selected, following variables such as % weight loss, % moisture (testa and cotyledon), pH (testa and cotyledon) and fermentation rate during fermentation and drying. The data were subjected to an analysis of variance by Anova and Tukey's multiple comparison tests at α= 0.05. The results showed a significant difference in terms of % cotyledon moisture, % testa moisture, cotyledon pH, testa pH and fermentation index, which suggests the difference that exists in fermenting materials, which can influence the sensory quality of cocoa produced in Colombia, which are mostly mixtures.